PRINCIPLES FOR EXECUTION OF ADAPTIVE MICROPROCESSOR CURRENT PROTECTION AGAINST INTER-PHASE SHORT-CIRCUITS - F. A. Romaniuk; A. A. Tishechkine; A. V. Kovalevsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The problem pertaining to maintenance of current protection sensitivity against inter-phase short-circuits is considered in the paper. The paper proposes a principle for execution of adaptive microprocessor current protection that makes it possible to increase sensibility factor and lower restriction on application of the given kind of protection.